Effect of a 36-month Pharmaceutical Care Program on the Coronary Heart Disease Risk in Elderly Diabetic and Hypertensive Patients - Paulo Roque Obreli Neto; Srecko Marusic; Divaldo Pereira de Lyra Júnior; Diogo Pilger; Joice Mara Cruciol-Souza; Walderez Penteado Gaeti; Roberto Kenji Nakamura Cuman (Frontiers Media S.A., 2011)
Purpose. To examine the effect of a pharmaceutical care program on the coronary heart disease risk in elderly diabetic and hypertensive patients. Methods. A total of 200 elderly (> 60 years) diabetic and/or hypertensive patients were recruited into a randomized, controlled, prospective clinical trial with a 36-month follow-up, developed in a public primary health care unit in a municipality in the Brazilian State of Sao Paulo. A range of clinical measurements were evaluated at the baseline and up to 36 months afterwards. The intervention group patients received pharmaceutical care from a clinical pharmacist, whereas the control group patients received their usual care from the medical and nursing staff. The Framingham scoring method was used to estimate changes in the 10-year coronary heart disease risk scores of all the patients. Results. A total of 194 patients completed the study. Significant reductions (p < 0.05) in the mean values (baseline vs. 36 months) for the systolic blood pressure [156.7mmHg vs 133.7mmHg; p